2011
DOI: 10.1111/j.1447-0756.2011.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation status of endometriosis: Epigenetics as the pathogenesis, biomarker and therapeutic target

Abstract: Endometriosis, a common, benign, estrogen-dependent disease affecting 3-10% of women of reproductive age, is characterized by the ectopic growth of endometrial tissue that is found primarily in the peritoneum, ovaries and rectovaginal septum. Recently, endometriosis has been alternatively described as an immune disease, a genetic disease and a disease caused by exposure to environmental factors, in addition to its usual description as a hormonal disease. In addition, accumulating evidence suggests that various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 123 publications
(278 reference statements)
2
65
0
8
Order By: Relevance
“…The epigenetic mechanisms represent a heritable dynamic and reversible means of modulating gene expression. The reversible nature of epigenetic aberrations is an important characteristic, since it allows us to search for appropriate pharmacological treatments, or 'epigenetic therapies' (25). In a number of studies it was demonstrated that RASSF1A expression was significantly increased or markedly upregulated in a number of types of cancer, including ovarian cancer and endometrial carcinoma, after treatment with 5-aza-DC (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic mechanisms represent a heritable dynamic and reversible means of modulating gene expression. The reversible nature of epigenetic aberrations is an important characteristic, since it allows us to search for appropriate pharmacological treatments, or 'epigenetic therapies' (25). In a number of studies it was demonstrated that RASSF1A expression was significantly increased or markedly upregulated in a number of types of cancer, including ovarian cancer and endometrial carcinoma, after treatment with 5-aza-DC (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Mindegyik DNMT-enzim génje endometriosisos sejtekben hipermetilálódik, ami fokozott génexpresszió-hoz vezet. Miután e gének működése szoros kapcsolatban van a kromatinszerveződés folyamataival is, így mű-ködésváltozásaik két epigenetikai mechanizmusrendszer (DNS-metiláció, kromatinszerveződés) működésével is összefüggést mutatnak [36].…”
Section: Epigenetikai Mechanizmusok Az Endometriosis Kialakulásának Hunclassified
“…Miközben a csökkenés mindkét progeszteronreceptortípust érinti, egyszersmind a PR-A:PR-B arány megváltozása is jellegzetes, az endometriosisra jellemző jelenség. Néhány évvel ezelőtt kutatási eredmények szá-moltak be a PR-B génjének hipermetilációjáról endometriosisban, amely downreguláció révén a progeszteronhatás felfüggesztődését okozza [36,40]. Wu vizs gálati eredményei azt is felvetették, hogy a PR-B génjének hipermetilációja a krónikus gyulladás kapcsán TNF-alfa hatására jön létre, vagyis az epigenetikai vál-tozás stimulációját maga a gyulladás jelenti [41].…”
Section: Epigenetikai Mechanizmusok Az Endometriosis Kialakulásának Hunclassified
See 1 more Smart Citation
“…In addition, estrogen-β receptor, steroidogenic-1factor and aromatase also underwent hypomethylation. 46 Inhibition of the E-cadherin expression due to hypermethylation causes disruption of cell adhesion, thus inducing invasion and metastasis of endometrial cells. HOXA10 genes in humans is expressed in the endometrium that is regulated by estrogen and progesterone.…”
Section: Epigenetic and Endometriosismentioning
confidence: 99%